2007
DOI: 10.1051/0004-6361:20066276
|View full text |Cite
|
Sign up to set email alerts
|

Surface heterogeneity of 2005 UD from photometric observations

Abstract: Context. The recently discovered Apollo-type near-Earth asteroid 2005 UD has been suggested to be a fragment of (3200) Phaethon. Aims. To test this hypothesis, we carried out photometric observations of 2005 UD using the 1-m telescope at Lulin Observatory. Methods. Multi-color photometry was used to compare the surface properties of (3200) Phaethon and 2005 UD. Surface-color variation due to the rotation was also examined. Conclusions. The similarity of surface colors between (3200) Phaethon and 2005 UD observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 19 publications
3
42
1
1
Order By: Relevance
“…For example, Ohtsuka et al (2006) identified an Apollo-type NEA 2005 UD that shows an orbit similar to that of 3200 Phaethon. Broadband photometry of 2005 UD revealed that it has blue optical colors that resemble those of Phaethon, consistent with the hypothesis that these two bodies have a common origin Kinoshita et al 2007). Moreover, another Apollo asteroid 1999 YC was found to be dynamically associated with 3200 Phaethon and 2005 UD (Ohtsuka et al 2008).…”
Section: Introductionsupporting
confidence: 78%
“…For example, Ohtsuka et al (2006) identified an Apollo-type NEA 2005 UD that shows an orbit similar to that of 3200 Phaethon. Broadband photometry of 2005 UD revealed that it has blue optical colors that resemble those of Phaethon, consistent with the hypothesis that these two bodies have a common origin Kinoshita et al 2007). Moreover, another Apollo asteroid 1999 YC was found to be dynamically associated with 3200 Phaethon and 2005 UD (Ohtsuka et al 2008).…”
Section: Introductionsupporting
confidence: 78%
“…They identified asteroid 2005 UD, classified as an Apollo type, as having a common origin with 3200 Phaethon (Ohtsuka et al 2006). Subsequent photometry of 2005 UD revealed that it has unusual blue optical colors like those of Phaethon, consistent with the idea that these two bodies have a common origin Kinoshita et al 2007).…”
Section: Introductionmentioning
confidence: 80%
“…This object is dynamically associated with the Geminid meteor stream (e.g., Williams & Wu 1993) and with several other small asteroids including 2005 UD (Ohtsuka et al 2006;Konoshita et al 2007) and 1999 YC (Ohtsuka et al 2008;Kasuga & Jewitt 2008). All these objects may be related to a precursor body that disintegrated ∼10 3 yr ago (Ohtsuka et al 2006).…”
Section: Observations Of Active Asteroidsmentioning
confidence: 92%